Die ou-Kersaandgesprek van Friedrich Schleiermacher in Afrikaans: Agtergrond, vertaling en hermeneutiek - Aarde, Andries van (HTS teologiese studies, 2003)
The Christmas Eve Dialogue of Friedrich Schleierma-cher in Afrikaans: Background, translation and herme-neuticsIn his Christmas Eve Dialogue (Die Weinachtsfeier: Ein Gespräch), Schleiermacher reflected on the theological tension between the quest for the historical Jesus and the dogma of the incarnation of Christ as “true God” and “true human”. In the fashion of his Romantic contemporaries, Schleiermacher presented his theology in the form of a story about friends celebrating Christmas Eve and their thoughts on the meaning of Jesus’ birth in their lives. This story was written in 1805 and printed in Gothic German in 1843. The aim of this article (the first of a series) is to translate Schleiermacher’s Christmas Eve Dialogue in Afrikaans. This article gives a brief biographical overview of Schleier-macher’s life and discusses the theoretical premises of his hermeneutics. After the translation of the first part of the Christmas Eve Dialogue (pages 465-472 in the 1843 printed edition), the article concludes with an explanation of the reasons why he would write such a story.